Satisfaction of nutritionists who work in food service - da COSTA, Rayane Luizi; STANGARLIN-FIORI, Lize; Labronici BERTIN, Renata; Opolski MEDEIROS, Caroline (Revista de Nutrição, 2023)
Objective To evaluate the job satisfaction of nutritionists who work in food service in the state of Paraná (Brazil). Methods A survey was carried out with 249 nutritionists through a semi-structured online questionnaire, which assessed their profi le, professional activities, and job satisfaction. The Mann-Whitney and Kruskal-Wallis tests and the ordinal logistic regression at a 5% signifi cance level were applied to evaluate the differences and relationship between job satisfaction and the independent variables. Results The average age of the survey participants was 31.9±6.4 years, the majority was female (95.58%), and graduated between 2000 and 2016 (90.36%). The survey revealed that 55.41% of the nutritionists were satisfi ed at work, 33.68% were indifferent, 6.86% were highly satisfi ed, and 4.04% were dissatisfi ed. The variables that infl uenced job satisfaction the most were age, years of training, income, and workdays in the week. Income explained satisfaction positively. There was statistical difference in relation to the satisfaction of participants regarding their knowledge on food service (p=0.0350), completion of postgraduate courses (p=0.0082), and interest in working in an area of nutrition other than food service (p<0.0001). Conclusion Although most professionals are satisfied, many were indifferent to job satisfaction, which may reflect a low perspective on their current job or poor experience in the food service. These results suggest the need for further actions aiming at raising nutritionists’ perceived professional importance.